Recent Advances in Industrial and Applied Mathematics - Chacón Rebollo, Tomás; Donat, Rosa; Higueras, Inmaculada (SEMA SIMAI Springer Series; ICIAM 2019 SEMA SIMAI Springer Series, 2022)
This open access book contains review papers authored by thirteen plenary invited speakers to the 9th International Congress on Industrial and Applied Mathematics (Valencia, July 15-19, 2019). Written by top-level scientists recognized worldwide, the scientific contributions cover a wide range of cutting-edge topics of industrial and applied mathematics: mathematical modeling, industrial and environmental mathematics, mathematical biology and medicine, reduced-order modeling and cryptography. The book also includes an introductory chapter summarizing the main features of the congress. This is the first volume of a thematic series dedicated to research results presented at ICIAM 2019-Valencia Congress.